Analisis kerusakan dan strategi perawatan pada ketel uap pipa air Miura Eh – 750F di Workshop Politeknik Pelayaran Sumatera Barat - Syamsyir, Syamsyir; Yanti , Melda; Devin , Hasri (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Pumps play an important role in moving fluids from one place to another. In this study, the Ebara 125 x 100 FS4KA centrifugal pump was used. The thing that made the author interested in conducting this research was the reduction in the performance of the centrifugal pump to circulate water from the training pool to the holding tank and back to the pool. The aim of this was to determine the factors causing the decline in the performance of the centrifugal pump. The method used is observation through data collection and data processing, data obtained from the field, namely wear and tear on the impeller diameter, which greatly influences pump performance. Before the pump was repaired with an impeller diameter of 245 mm, the pump capacity was 78 m3/hour, the pump hydraulic power was 5.8 Kw, the pump head was 27.4 m, the pump efficiency was 43.20%, and the fluid speed was 1,014 m/sec. After repairing the Ebara 125 x 100 FS4KA centrifugal pump by replacing the impeller size by 250 mm, the performance of the Ebara 125 x 100 FS4KA centrifugal pump increased by 80 m3/hour, pump hydraulic power 6.04 KW, pump head 28 m, pump efficiency of 45.24%, and fluid velocity of 1,032 m/sec.